- #1

Tangent...

- 8

- 0

## Homework Statement

I'm trying to show equivalence of two statements:

Let f:S-->T be a function, show that f is 1-1 (injective) is equivalent to f(A n B) = f(A) n f(B) for all A,B subsets of S.

## The Attempt at a Solution

I know equivalence means iff, so I started by assuming f is 1-1 and showing f(A n B) = f(A) n f(B) by showing containment both ways (I think I did that part right, since f(A n B) subset of f(A) n f(B) is easy, and f(A) n f(B) subset of f(A n B) uses the fact that f is 1-1).

Now I assume f(A n B) = f(A) n f(B) and try to show f is 1-1. I let x,y be elements of S such that f(x) = f(y). And I don't know where to go from here. I guess I don't know how to combine f(x) = f(y) and f(A n B) = f(A) n f(B) but I'm pretty sure I have to, somehow. Any tips would be greatly appreciated. Thanks!